2021
DOI: 10.1038/s43018-021-00238-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PUS7 suppresses tRNA pseudouridylation and glioblastoma tumorigenesis

Abstract: Pseudouridine is the most frequent epitranscriptomic modification. However, its cellular functions remain largely unknown. Here we show that the pseudouridine synthase PUS7 is highly expressed in glioblastoma versus normal brain tissues, and high PUS7 expression levels are associated with worse survival in glioblastoma patients. The PUS7 expression and catalytic activity are required for glioblastoma stem cell (GSC) tumorigenesis. Mechanistically, we identified PUS7 targets in GSCs through small RNA pseudourid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 72 publications
2
70
0
Order By: Relevance
“…reported that the expression and catalytic activity of PUS7 are critical for tumorigenesis. 73 Taken together, the above results indicate the potential importance of RNA modification activity for cancer screening and diagnosis.…”
Section: Multi-omics For Biomarker Discovery For Early Diagnosis Of Ocmentioning
confidence: 63%
“…reported that the expression and catalytic activity of PUS7 are critical for tumorigenesis. 73 Taken together, the above results indicate the potential importance of RNA modification activity for cancer screening and diagnosis.…”
Section: Multi-omics For Biomarker Discovery For Early Diagnosis Of Ocmentioning
confidence: 63%
“…Stand-alone pseudouridine synthase-catalyzed introduction of pseudouridines is well established in tRNAs and spliceosomal snRNAs ( Spenkuch et al, 2014 ), but has also recently been found in mRNAs ( Borchardt et al, 2020 ) in several eukaryotic organisms, including plants ( Sun et al, 2019 ). Since pseudouridylation of tRNA can be important for translation of specific mRNAs encoding regulatory factors ( Cui et al, 2021 ) and snRNA pseudouridylation is linked to growth habit and stress adaptation in yeast, presumably via effects on alternative splicing ( Morais et al, 2021 ), the use of alternative PUS5 isoforms with distinct subcellular localization could have important ramifications for PTI-associated genetic reprogramming.…”
Section: Resultsmentioning
confidence: 99%
“…Since it is the most common type of primary brain tumors and accounts for 81% of primary malignant intracranial tumors in human 35 , glioma is of intensive interest. Among three types of human gliomas, low-graded astrocytoma (A), anaplastic astrocytoma (AA), and glioblastoma (GBM) 28 , 35 , GBM is the most lethal one 36 38 . The median survival of patients with GBM remains < 16 months after diagnosis 39 .…”
Section: Discussionmentioning
confidence: 99%